2017
DOI: 10.7863/ultra.16.03049
|View full text |Cite
|
Sign up to set email alerts
|

Primary Mural Endocarditis Without Valvular Involvement

Abstract: Primary mural endocarditis is an extremely rare infection in which nonvalvular endocardial involvement is seen without any cardiac structural abnormalities such as ventricular septal defects. The rapid and precise diagnosis of this disease remains challenging. We present 2 cases (67- and 47-year-old male patients) of pathologically confirmed primary mural endocarditis that could have been detected by initial transthoracic echocardiography in the emergency department. Transthoracic echocardiography and transeso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Previous cases have reported failure of antimicrobial therapy alone in resolution of mural endocarditis. 2 In our case, however, the patient was successfully treated using conservative methods given no evidence for serious complications, and there was clinical improvement and resolution of vegetations with antimicrobial therapy. Annular thickening was presumably related to endocardial or myocardial inflammation in this case and remained unchanged.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Previous cases have reported failure of antimicrobial therapy alone in resolution of mural endocarditis. 2 In our case, however, the patient was successfully treated using conservative methods given no evidence for serious complications, and there was clinical improvement and resolution of vegetations with antimicrobial therapy. Annular thickening was presumably related to endocardial or myocardial inflammation in this case and remained unchanged.…”
Section: Discussionmentioning
confidence: 61%
“…1,7,8 The most common causative organisms of mural endocarditis include S aureus, Streptococcus species, Candida species, and Aspergillus species. 2 Our patient is the second reported case of primary mural endocarditis caused by group A beta hemolytic Streptococcus bacteremia; the first involved a 3-year-old girl with a history of developmental delay and Chiari malformation in 1992. 9 S pyogenes is an overall rare cause of infective endocarditis in any age group.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Non-valvular endocardial infections are often secondary to valvular vegetations, regurgitation, prosthetic valves and congenital shunts; however, primary mural endocarditis occurs without any cardiac structural abnormalities 1 2. Tahara et al performed a Medline literature search and reported only 19 cases of primary mural endocarditis since 1986 2. Transthoracic and transoesophageal echocardiograms remain the standard of care for prompt diagnosis of this disease process 2.…”
Section: Descriptionmentioning
confidence: 99%
“…Tahara et al performed a Medline literature search and reported only 19 cases of primary mural endocarditis since 1986 2. Transthoracic and transoesophageal echocardiograms remain the standard of care for prompt diagnosis of this disease process 2. Yet, patients commonly opt against transoesophageal echocardiogram due to invasive approach or sedation requirements.…”
Section: Descriptionmentioning
confidence: 99%